Implications of Integrating Women into the Marine Corps Infantry - Schaefer, Agnes Gereben (RAND Corporation, 2015)
This study for the U.S. Marine Corps presents a historical overview of the integration of women into the U.S. military and explores the importance of cohesion and what influences it. The gender integration experiences of foreign militaries, as well as the gender integration efforts of domestic police and fire departments, are analyzed for insights into effective policies. The potential costs of integration are analyzed as well.